Peningkatan Quality Rate pada Batang Rokok SKT di Industri Rokok - Debora Anne Yang Aysia; Aditia Karuniawan; Fiona Evangeline (Universitas Merdeka Malang, 2025)
The research was conducted at a Kretek cigarette factory in Surabaya. Data from the Quality Assurance Department shows the quality rate for regular SKT products is 87.69%, which has yet to reach the company's target of 89%. This research follows the DMAIC stages with the help of quality tools in the form of Pareto charts and five whys analysis. From the results of the Pareto chart, it was found that the five highest types of defects with an accumulated percentage of 79% were defects in middle ambry glue, end ambry glue, flat or flat, small heads, and dirty or corroded. Root cause analysis is carried out with the help of 5 whys analysis. The root causes of defects include workers who are negligent and in a hurry, lack of tools, no work method provisions, and no check or inspection schedule. Implementation of improvements to address the root causes is carried out through improving work methods such as re-gluing methods on ambry, adjusting production targets, improving the deposit of milled products, changing the placement of basins for workers' hand wipes, and work methods related to workers' hand hygiene. In addition to improving work methods, unannounced inspections were carried out by milling assistants, regular reminders regarding work instructions, and the addition of work tools in the form of ambry racks, blend filling indicator signs and changing the color of the ambry receiving line. Implementing improvements resulted in an increase in the quality rate to 90.87%. Making work instructions, action plans, checklists, and tool specification documents is carried out to maintain the results of improvements in the production process. Penelitian dilakukan di salah satu pabrik rokok kretek di Surabaya. Data dari Departemen Quality Assurance menunjukkan quality rate produk SKT reguler sebesar 87,69%, yang belum mencapai target perusahaan sebesar 89%. Penelitian ini mengikuti tahapan DMAIC dengan bantuan quality tools berupa pareto chart dan 5 whys analysis. Dari hasil pareto chart ditemukan 5 jenis kecacatan tertinggi dengan akumulasi persentase sebesar 79% berupa kecacatan lem ambri tengah, lem ambri ujung, kempis atau gembos, kecil kepala, dan kotor atau korep. Analisis akar penyebab dilakukan dengan bantuan 5 whys analysis. Akar penyebab dari kecacatan berupa pekerja yang lalai dan tergesa-gesa, kurangnya alat bantu, belum ada ketentuan metode kerja, dan belum ada jadwal pengecekan maupun inspeksi. Implementasi perbaikan untuk mengatasi akar penyebab dilakukan melalui perbaikan metode kerja seperti metode pengeleman ulang pada ambri, penyesuaian target produksi, pembenahan penyetoran hasil giling, perubahan penempatan baskom untuk lap tangan pekerja, dan metode kerja terkait kebersihan tangan pekerja. Selain perbaikan metode kerja dilakukan inspeksi mendadak oleh asisten giling, pengingat rutin terkait instruksi kerja, dan penambahan alat kerja berupa rak ambri, rambu indikator pengisian blend, dan penggantian warna garis terima ambri. Implementasi perbaikan menghasilkan peningkatan pada quality rate menjadi 90,87%. Pembuatan work instruction, action plan, checklist, dan dokumen spesifikasi alat dilakukan untuk mempertahankan hasil perbaikan dalam proses produksi.